Can a Legislative Assembly Function without an Executive Government under the Indian Constitution? - DAM, Shubhankar (Institutional Knowledge at Singapore Management University, 2008)
Can the Governor dissolve a Legislative Assembly under the Indian Constitution even before convening its first meeting on the ground that no party had adequate mandate to form the government? That was the question posed before the Supreme Court in Rameshwar Prasad. The Court held in the affirmative. For the Court, a Legislative Assembly can be brought into existence only when some members of the Legislature are in a position to form the Executive Government (the Cabinet). This short comment proposes an argument to the contrary. I argue that the Supreme Court's conclusion was made possible by a method of qualified silence. The comment identifies three forms of qualified silence in the text of the judgment and argues that in so concluding the Court inverted the normative positions of the Legislature and the Executive. In a parliamentary democracy, where the Legislature legitimises public institutions and offices including those of the Executive, the relationship must be otherwise.